Act of Feb. 16, 1787, ch. VI, 1787 Mass. Acts 555 - (:unkn) unknown (General Publisher, 1787)
Required persons against the Government to deliver their arms to a justice of the peace and “subscribe the oath of allegiance to this Commonwealth.”
--
Keywords: POSSESSION - DANGEROUS PERSONS